If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -2) + 3(3x + -1) = 4(x + -3) + 7x Reorder the terms: 5(-2 + x) + 3(3x + -1) = 4(x + -3) + 7x (-2 * 5 + x * 5) + 3(3x + -1) = 4(x + -3) + 7x (-10 + 5x) + 3(3x + -1) = 4(x + -3) + 7x Reorder the terms: -10 + 5x + 3(-1 + 3x) = 4(x + -3) + 7x -10 + 5x + (-1 * 3 + 3x * 3) = 4(x + -3) + 7x -10 + 5x + (-3 + 9x) = 4(x + -3) + 7x Reorder the terms: -10 + -3 + 5x + 9x = 4(x + -3) + 7x Combine like terms: -10 + -3 = -13 -13 + 5x + 9x = 4(x + -3) + 7x Combine like terms: 5x + 9x = 14x -13 + 14x = 4(x + -3) + 7x Reorder the terms: -13 + 14x = 4(-3 + x) + 7x -13 + 14x = (-3 * 4 + x * 4) + 7x -13 + 14x = (-12 + 4x) + 7x Combine like terms: 4x + 7x = 11x -13 + 14x = -12 + 11x Solving -13 + 14x = -12 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -13 + 14x + -11x = -12 + 11x + -11x Combine like terms: 14x + -11x = 3x -13 + 3x = -12 + 11x + -11x Combine like terms: 11x + -11x = 0 -13 + 3x = -12 + 0 -13 + 3x = -12 Add '13' to each side of the equation. -13 + 13 + 3x = -12 + 13 Combine like terms: -13 + 13 = 0 0 + 3x = -12 + 13 3x = -12 + 13 Combine like terms: -12 + 13 = 1 3x = 1 Divide each side by '3'. x = 0.3333333333 Simplifying x = 0.3333333333
| x^2+2x-1512=0 | | 26+6x=4(x+15) | | x+6=3x*2 | | -2x-4x-2=1 | | (9x-25)/(4x-9) | | 9/5-6=12 | | 2x^3+x^2-8x-16=0 | | -z/3=6 | | 3(a-2)=4a-(a+2) | | 16=-8+5/-7 | | 4+3y=12 | | -6=-3/8u | | 3x+0.5y=0.5 | | -4x-30=9(x+1) | | 9x^2-24x+16-16+x^2=0 | | 2m-6=m+16 | | 4x-7=-5+2x | | 16t^2+128t-192=0 | | 4x-5+3x+1+x+25= | | 3s=14+10s | | m=-2-(-1)/-4-3 | | 75=-5x-3(2x+8) | | 25x^4-30x^3+9x^2=0 | | 49y^2-7y+1/4=0 | | 2x+(-1)=-11 | | 8x-3x-6=4 | | 9b^2= | | (K+2)2=16 | | 149=-4x-3(4x-7) | | 11/2+21/2+36 | | 14n^2+23n-15=0 | | 9/5x-6=12 |